2018
DOI: 10.1504/ijplm.2018.094714
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shipbuilding and construction industries from the product structure standpoint

Abstract: The use of building information modelling (BIM) in construction compares to the use of product lifecycle management (PLM) in manufacturing. Previous research has shown that it is possible to improve BIM with the features and the best practices from the PLM approach. This article provides a comparison from the standpoint of the bill of materials (BOM) and product structures. It compares the product beginning of life in both construction and shipbuilding industries. The research then tries to understand the use,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…Although the results of this study are based on experience from the construction industry, they allow us to hypothesize that the distance teaching of other technological approaches similar to BIM could benefit from the conclusions of the study in other industrial fields where similar issues are observed. We can think, for example, of the distance teaching of Product Lifecycle Management (PLM) in the manufacturing industry, which is often compared to BIM because of the multiple similarities between the two approaches [30,31]. In addition, the academic constraints and the educational context-as summarized by Maranzana et al [32] for PLM education-seem very similar to the issues identified in BIM education in construction [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of this study are based on experience from the construction industry, they allow us to hypothesize that the distance teaching of other technological approaches similar to BIM could benefit from the conclusions of the study in other industrial fields where similar issues are observed. We can think, for example, of the distance teaching of Product Lifecycle Management (PLM) in the manufacturing industry, which is often compared to BIM because of the multiple similarities between the two approaches [30,31]. In addition, the academic constraints and the educational context-as summarized by Maranzana et al [32] for PLM education-seem very similar to the issues identified in BIM education in construction [2].…”
Section: Discussionmentioning
confidence: 99%
“…The life cycle of a built facility can be broken down into several phases. Basing from previous works (Neufert, 2002;Boton, 2013;Boton et al, 2018), we can classify these phases into the pre-project phase (assembly, feasibility studies, and search for funding), the pre-construction phase (design, allotment, allocation of lots, and site preparation), the construction phase (construction of the structure), and the post-construction phase (reception, operation, rehabilitation, or demolition).…”
Section: It In the Construction Industry 211 Peculiarities Of The Cmentioning
confidence: 99%
“…Increasing levels of BIM maturity across design and construction activities are being documented in the literature, and project activities, which were once dispersed and siloed, are slowly being integrated via digital project delivery methods (Boton et al 2017). With such changes to project delivery, opportunities for integrated, model-based approaches to information management in operations are beginning to be realized.…”
Section: Introductionmentioning
confidence: 99%